EFEKTIVITAS PENDEKATAN QUANTUM TEACHING DALAM MENINGKATKAN PEMAHAMAN KONSEP PENGURANGAN BAGI ANAK TUNARUNGU - Sari Nursulawati (Jurnal Penelitian Pendidikan Khusus, 2014)
Abstract : This research is motivated by the problems faced by deaf clients in special classes D/2/B  in SLB Wacana  Asih Padang , namely the reduction in student understanding of the concept is very minimal. In fact, from day to day demands of KKM is very increased . However , the deaf client has not been able to understand the concept of reduction though only on the ability of the base . To overcome these problems need to find a way out , so that children are able to understand the concept of subtraction . Then conducted an experimental study to determine the ability to form understanding of the concept of reduction in the client . This type of research is a Quasi- Experiment , pretest - posttest experimental design is implemented in one group without using the comparison group . The subjects were four deaf clients in special classes D/2/B in SLB Wacana  Asih Padang . Data obtained using the test works . Analysis of the data used is the Mann-Whitney U test with hypothesis testing criteria accepted if Uhit > UTab and conditions beyond the hypothesis is rejected at the 95 % significance level or α = 0.05 level . The results of data processing show UTab Uhit = 0.5 and = 0 , meaning that the hypothesis is accepted . So the results showed that the approach is Quantum Teaching affect the understanding of the concept of reduction in class deaf clients D/2/B in SLB Wacana  Asih Padang . To that end , the school advised to always provide a diverse learning revolution in order to increase interest and improve students' skills in all subjects , especially math .   Kata kunci: Tunarungu: Kosep pengurangan; Pendekatan Quantum Teaching